The Effectiveness of Kepok Banana on The First Trimester Emesis Gravidarum - Debora Paninsari; Kurniawati Buulolo; Lioni Masta Lubis; Manja Riskawati Riskawati; Mariani Br Panjiatan (Jurnal Penelitian Perawat Profesional, 2020)
Emesis gravidarum causes changes in the body's metabolism due to dehydration and it occurs due to a decrease in the mother's appetite. Continuous gravidarum emission will continue for the health of the mother and the development of the fetus she is carrying. This study aims to see the effectiveness of Kepok Banana against nausea and vomiting in pregnant women at the Clinic Midwife Sunggal Medan in 2020. This research method is quantitative analytic observational with this type of research design using pre-experimental design is one group pretest-potest. The study was conducted on August 4 to September 1 2020 with a population of 63 people and a sample of 30 people using the Accidental Sampling technique. Aspects of data measurement using observation sheets with bivariate data analysis. The results showed that all respondents (100%) experienced a decrease in nausea and vomiting. The results of data analysis obtained Z value = -5.477ᵇ and p-value = 0.000 with a significance level of p <0.05.